The Effect of The TED-Ed Application on Students Word Recognition in Listening at SMPN 47 Bekasi - Chardina Umi Zar’in; Ika Chairiyani; Rini Septa Angraini (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The objective of this research was to investigate the effect of using the TED-Ed application on students’ word recognition in listening skills. This study employed a pre-experimental method with a one-group pre-test and post-test design. The population consisted of all eighth-grade students of SMPN 47 Bekasi, totaling 210 students, while the sample of 35 students was selected through purposive sampling. The instrument used was a multiple-choice word recognition test administered before and after the treatment. Data analysis was conducted using the Shapiro-Wilk test for normality and the Wilcoxon Signed-Rank Test for hypothesis testing due to the data being not normally distributed. The results revealed a significant difference between students’ pre-test and post-test scores after being taught with the TED-Ed application, as shown by an Asymp. Sig. (2-tailed) value of p < 0.001 < 0.005. This indicates that the use of TED-Ed positively influenced the improvement of students’ word recognition in listening. These findings highlight the potential of technology-based learning media in enhancing English language teaching strategies, particularly in supporting students’ listening comprehension, and suggest that interactive platforms like TED-Ed can serve as effective tools to create engaging and meaningful learning experiences.